Correlation between Adolescents’ Temperament and Internet Addiction Levels in Junior High School in Surabaya, Indonesia - Destasari Tri Hartanti; Yunias Setiawati; Dominicus Husada; Irwanto Irwanto (Jurnal Berkala Epidemiologi, 2021)
Background: Internet addiction has become a serious problem in the world, especially for adolescents. Temperament plays an important role in influencing internet addiction in adolescents. Purpose: The aim of this study was to analyze the relationship between students’ characteristics and temperament with their internet addiction levels in one of the junior high schools in Surabaya, Indonesia. Methods: This was a cross-sectional study, which used primary data that was obtained from students who filled out a questionnaire. The study sample included 114 students in one of the junior high schools in Surabaya. The dependent variable was the internet addiction level; the dependent variables were gender, age, student grade, and temperament. An Internet Addiction Test (IAT) and an Early Adolescents Temperament Questionnaire-Revised (EATQ-R) were the tools used for data collection. Data was collected in November 2019. The sample selection was done through the stratified random sampling technique. The data was subsequently analyzed using the Fisher’s exact and Spearman correlation tests. Results: There was a significant positive correlation between age (p<0.01), student grade (p<0.05), negative affectivity (p<0.01), and surgency (p<0.05) toward internet addiction levels. There was a significant negative correlation observed between effortful control (p<0.05) and internet addiction levels. Conclusion: There was a significant relationship between age, student grade, negative affectivity, surgency, and effortful control and adolescents’ internet addiction levels.